A preliminary study of stress in higher education and contributing factors to lecturers - Isa, Khairunesa; Palpanadan, Sarala Thulasi (Science and Engineering Research Support Society, 2020)
A flexible working hour is one of the advantages for most lecturers. However, the settings of too much key performance index (KPI) based on 7 indicators that need to be achieved tend to cause the lecturers stress. This preliminary study was carried out to identify the factors that significantly contribute to lecturers’ stress. A total of 40 academicians were selected as respondents from three selected university which was under the cluster Comprehensive University, Research University and Focus University. This preliminary study found that the stress level among Malaysian lecturers were at low moderate level with mean value 2.40. Significantly the work load and job activities, networking, health and personal of lecturers have contributions to the level of their stress even in simple moderate level. This finding directly showed that Malaysian lecturers still can manage their daily work routine and control their stress level. It can be assumed that all lecturers have great passion to be lecturers, and thus, they can cope with the 7P loads and face various challenges. In addition, the element of belief in God helps the lecturers to proceed with their carriers peacefully.